Psicología del deporte y ciencias aplicadas - Espinosa Gómez, Josman (Universidad Autónoma de Nuevo León, 2020)
The Centro de Enseñanza Técnica y Superior (CETYS) Mexicali campus has a large number of high-performance athletes in various disciplines. Belonging to a representative team at CETYS University, gives rise to the students being in a situation of stress and/or anxiety to maintain their scholarship or present difficulties in organizing their sleep schedule, eating habits, homework, tasks, etc. The present study, in its first stage, seeks to define the profile of the high-performance student-athlete of CETYS University campus Mexicali to detect their needs and how sports psychology could benefit them. This research was raised from a mixed approach, and is intended to be descriptive and transversal in design. The sample was made up of 26 high-performance student-athletes from CETYS University campus Mexicali, as well as managers and coaches in charge of the sports arena, from both individual and team disciplines. Clinical history, laterality test and incomplete sentences were applied; Afterwards, the codification of the data obtained, definition and development of categories, interpretation and analysis of data were performed. It was found that both academic, family and social factors have a significant impact on the way they face difficult situations, as well as motivation, due to the demands such as maintaining a scholarship, meeting the expectations of their coaches and their families, as well as their own to succeed in the activities they perform
La psicología del deporte como factor de bienestar estudiantes atletas representativos de CETYS Universidad / The psychology of sport as a factor of well-being representative student athletes of CETYS University
Keywords: Sports psychology; Athletes; University; Wellbeing; Campus Mexicali